Designing Dormitory Student with Modern Architecture Concept at Universitas Sumatera Utara Kwala Bekala - Saragih, Sarah Nurdini; Amy Marisa (Talenta Publisher, 2023)
Universitas Sumatera Utara Kuwala Bekala does not have student dormitory facilities, which is the main reason for this project. The application of modern architecture in dormitory buildings is designed with a more minimalist impression and still has the aesthetics of the beauty of the modern building. Modern architecture uses the concept of